ISOLATION OF A FLAVONOID COMPOUND FROM APPLE (MALUS DOMESTICA BORKH.) LEAVES - Ristya Mustika Arum, Indah
Apple (Malus domestica Borkh., Rosaceae) is one of the commonly consumed fruits in the world, included Indonesia. In Indonesia, apples are imported or supplied from apple plantations. Due to location of Indonesia in tropical zone, defoliation is required to break the dormancy period of the plant. Up to now, apple leaves from defoliation are only used for fertilizer. According to some studies, the content of phenolic compounds in the apple leaves is greater than those in the apple peels. This research is focussed on isolation and characterization of phenolic compounds, especially flavonoid compounds from apple leaves. Crude drug of apple leaves was extracted by reflux using ethanol and monitored by thin layer chromatography (TLC). Hot water was added into the ethanol extract to separate chlorophyll. The ethanol extract was then fractionated by liquid-liquid extraction subsequently with n-hexane and ethyl acetate. The ethyl acetate fraction was subfractionated by radial chromatography and a compound was isolated from one of the subfraction by preparative TLC. The isolate was then purified and the purity of isolate was tested by TLC using three different mobile phases and by two-dimentional TLC. The pure isolate was characterized and identified by paper chromatography, UV-visible spectrophotometry, and IR-spectrophotometry. Crude drugs of apple leaves contained flavonoids, tannins, steroids and triterpenoids. The flavonoid compound isolated from the ethyl acetate fraction was paper chromatographed showing Rf values of 0.85 (mobile phase: n-butanolacetic acid-water, 4:1:5) and 0.33 (mobile phase: acetic acid 15%). The isolate gave maximum absorbance in wavelength of 281 nm (Band II) and 324 nm sh (Band I). The band II shifted 44 nm with NaOH, 40 nm with NaOAc, and 23 nm with AlCl3/HCl. There were -OH (3394.1 cm -1 ), -CH2- (2923.56 cm -1 and 2854.13 cm -1 ), C=O (1627.63 cm -1 ), and C=C in aromatic ring (1457.92 cm -1 ) in the isolate structure. The isolated compound was predicted as an aglycone flavanone with –OH groups in positions of C5 and C7.